Satu Pribadi, Dua Natur, dan Empat Injil: Menghindari Bahaya Nestorianisme dalam Studi Yesus Sejarah - Crowe, Brandon (STT Reformed Injili Internasional, 2024)
One of the most difficult flashpoints between biblical studies and confessional theology is the study of Jesus—whether we define this as studying the historical Jesus or studying Jesus historically—and thechurch’s creedal Christology. In this essay, I consider the dangers of Nestorianism in modern studies of Jesus. First, I outline the dangers and tensions between the study of the historical Jesus and the church’s creedalstatements about Christ. Second, I discuss the relationship between creeds and Scripture. Third, I consider briefly what we can say about Nestorianism, and how one arguably finds echoes of Nestorianism in modern approaches to the historical Jesus. Fourth, I offer six suggestions for a way forward for those who seek to honor both the church’s creedal traditions and the witness of the New Testament.